Essere-con. Il gruppo come evento e origine dell’evento. Sull’empatia (compassione) come elemento costitutivo del gruppo (istituzione) - Bojanić, Petar; Loddo, Olimpia G. (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The complementarity of the terms “group” and “event” is not accomplished in the title “Group as Event and Origin of Event.” My intention is to describe this very relation, which vacillates between interaction and equivalency, and appears in the encounter of the event and the group. This relation could therefore represent a preamble to a theory of institution or even an introduction to institutional action. In order to show that without a group there is no event, or that the group is the condition of something being named an event, and vice versa, that an event implies the existence of a group, I reconstruct the notion of “event”, drawing on my native language as well as the meaning of the word event in Russian [sobitie]. At the same time, I would like to thematize empathy (compassion) as the basic field of constituting a group and event, and as the beginning of the institution, that is, the institutional condition. Keywords: group, event, institution, compassion, empathy.